2013
DOI: 10.1155/2013/635140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Flux and Friction Coefficient on Thermal Stresses in Risers of Drum Boilers under Dynamic Conditions of Steam Demand

Abstract: Boiler swing rate, which is the rate at which the boiler load is changed, has significant influence on the parameters of the boiler operating conditions such as drum water pressure and level, steam quality in the riser tubes, wall temperatures of riser tubes, and the associated thermal stresses. In this paper, the thermal stresses developed in boiler tubes due to elevated rates of heat transfer and friction are presented versus thermal stresses developed in tubes operated under normal conditions. The different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The data contain 21,600 samples of SFR with sampling rate of 1 s. The behavior of all the other variables is simulated using Å stro¨m and Bell's model 7 of boiler. The results of that are validated against experimental data and extensively discussed in Elshafei et al 12 and Habib et al; 33 but using our PID gains, the entire system is simulated again as shown in Figure 4 to provide a modest overview of available results in the literatures.…”
Section: Experimental Afr Simulationsupporting
confidence: 60%
See 1 more Smart Citation
“…The data contain 21,600 samples of SFR with sampling rate of 1 s. The behavior of all the other variables is simulated using Å stro¨m and Bell's model 7 of boiler. The results of that are validated against experimental data and extensively discussed in Elshafei et al 12 and Habib et al; 33 but using our PID gains, the entire system is simulated again as shown in Figure 4 to provide a modest overview of available results in the literatures.…”
Section: Experimental Afr Simulationsupporting
confidence: 60%
“…The experimental AFR is used to present the main results of Elshafei et al, 12 Alzaharnah et al 17 and Habib et al 33 to have a composite summary of available literature. All these works including ours are based on a commonly acquired data from an industrial boiler installed in eastern province in Saudi Arabia.…”
Section: Experimental Afr Simulationmentioning
confidence: 99%